Synthesis and Anti-HIV Activity of Novel Macrocyclic Disuiphide Compounds with Thioreylene Group - Jhaumeer-Laulloo, B.S. (Asian Journal of Chemistry, 2010)
Macrocyclic compounds with thioureylene moiety were synthesized by condensing bis acid chloride with KSCN followed by diamines. These compounds were characterised using various spectral techniques (lR, NMR, mass spectra) and analytical data. The synthesized compounds were evaluated for their ability to inhibit reverse transcriptase (RT) of the human immunodeficiency virus HIV-1 (IIIB) in C8166 cells. The macrolide (VIII) containing a benzene disulphide bridge was found to be most potent and inhibited the replication of HIV-1 virus at a concentration of 1.6 μg/mL.